Eco-labelling and product development: potentials and experiences. (23rd September 2008) - Rubik, Frieder; Scheer, Dirk; Iraldo, Fabio
The last years promoted new policy instruments based on cooperation and aiming at a higher degree of voluntariness and self-regulation. Eco-labelling is a typical instrument applied in this context. Eco-labels award and promote environmentally superior goods and services and offer information on their quality and performance with respect to consumer health, resource consumption, and environmental impacts. We present an overview on the history and 'landscape' of eco-labels and explain objectives and mechanisms. Later, we examine potentials and experiences within business. In the following, an empirical view on the state, successes and failures of eco-labelling – primarily based on a meso- and macro-economic view – is presented. We close with consequences and challenges for strengthening eco-labelling.